152k views
0 votes
Question 13 and 14 please! Answer and show work :)

Question 13 and 14 please! Answer and show work :)-example-1

1 Answer

4 votes

Answer:

Problem 13)
f(x)=4\,sin((1)/(2) x+(2)/(3)\pi )-2

Problem 14)
f(x)=cotan(x+(1)/(3) \pi)+2

Explanation:

Recall how transformations affect the graph of the sine function, and how such is conveyed into the parameters A, B, C, and D that could be included in the general form of the function:


f(x)=A\,sin(Bx+C)+D

where the Amplitude of the transformed sine function is the absolute value of the multiplicative parameter A:

Amplitude =
|A|

The period is (which for sin(x) is
2\pi) is modified by the parameter B in the following manner:

Period =
(2\pi)/(B)

Where the phase shift is introduced as:

Phase shift =
-(C)/(B).

and finally any vertical shift is included by the constant D (positive means shift upwards in D many units, and negative means shift downwards D units)

Therefore, to have a sine function with the requested characteristics, we work on the value of the parameters A, B, C, and D one at a time:

1) Amplitude =
|A|=4 then we use parameter A = 4


f(x)=4\,sin(Bx+C)+D

2) Period
4\pi, then we work on the parameter B:

Period =
(2\pi)/(B)


4\pi=(2\pi)/(B)\\B*4\pi=2\pi\\B=(2\pi)/(4\pi) \\B=(1)/(2) which transforms the function into:


f(x)=4\,sin((1)/(2) x+C)+D

3) phase-shift =
-(4)/(3) \pi

Then knowing that B=
(1)/(2), we work on the value of parameter C:

Phase shift =
-(C)/(B)


-(4)/(3) \pi=-(C)/(B) \\-(4)/(3) \pi=-(C)/( (1)/(2) )\\-(4)/(3)* (1)/(2) \pi=-C\\C=(2)/(3) \pi

Therefore the function gets transformed into:


f(x)=4\,sin((1)/(2) x+(2)/(3)\pi )+D

4) and finally the vertical shift of negative two units, that gives us the value D = -2

The complete transformed function becomes:


f(x)=4\,sin((1)/(2) x+(2)/(3)\pi )-2

Now for problem 14, recall that the cotangent function is the reciprocal of the tangent function, therefore, their periodicity is the same:
\pi

since you are asked for a cotangent function of period
\pi as well, there is no multiplication parameter "B" needed (so we keep it unchanged - equal to one). B = 1

Then for the phase-shift which we want it to be
-(1)/(3) \pi, we set the condition:


-(1)/(3) \pi=-(C)/(B) \\-(1)/(3) \pi=-(C)/(1)\\-(1)/(3) \pi=-C\\C=(1)/(3) \pi

And insert such in the cotangent general form:


f(x)=cotan(x+(1)/(3) \pi)+D

and finally include the desired vertical shift of 2 units:


f(x)=cotan(x+(1)/(3) \pi)+2

User Sheniqua
by
5.7k points